Efeitos de diferentes angulações do Cymbol® na oscilação pressórica. - Nunes, Ana Giulia Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Cymbol® is amongst devices that use high frequency oscillation and positive expiratory pressure to improve mucociliary clearance in obstructive respiratory diseases, these are small, portable and inexpensive. Cymbol® offers resistance to exhaled air through the silicone film, opening and closing the air passage and producing pressure fluctuations. This article as to study the effects of different angulations on generation of positive expiratory pressure. Cymbol® was fixed to a support base and the angle was checked with a goniometer. The device was connected to a hose and it connected to a flow meter and the compressed air network. The results presented that the highest pressure amount were obtained at - 30 ° and the lowest amount at -15 °. Regarding the flow amount, the highest were also obtained at -30 ° and the lowest, also at -15 °. Considering such results, it is concluded that there is a clear influence of different angles of inclination on the oscillation of expiratory flows and pressure, consequently on the performance of Cymbol® and its effects on secretion mobilization.

Dentre os dispositivos que utilizam a oscilação de alta frequência e pressão expiratória positiva melhoram a depuração mucociliar nas doenças respiratórias obstrutivas está o Cymbol®, esses são pequenos, portáteis e de baixo custo. O Cymbol® oferece resistência ao ar exalado por meio da película de silicone, abrindo e fechando a passagem de ar e produzindo oscilações de pressão. O estudo tem como objetivo estudar os efeitos das diferentes angulações na geração de pressão expiratória positiva. O Cymbol® foi fixado a uma base de apoio e o ângulo conferido com um goniômetro. O dispositivo foi conectado a uma mangueira adaptada, e a mesma conectada a um fluxômetro e a rede de ar comprimido. Os resultados apresentaram que os maiores valores de pressão foram obtidos na angulação de - 30° e os menores valores, em -15°. Em relação aos valores de fluxo, os maiores também foram obtidos em -30° e os menores, também em -15°. Considerando tais resultados, conclui-se que há uma clara influência de diferentes ângulos de inclinação na oscilação dos fluxos expiratórios e na pressão, consequentemente no desempenho do Cymbol® e nos seus efeitos sobre a mobilização da secreção.
Effects of different angles of Cymbol® on pressure oscillation.
Keywords: Physical therapy; Respiratory therapy; Airway management; Breathing exercises; Fisioterapia; Terapia respiratória; Manuseio das vias aéreas; Exercícios respiratórios